Study of the relationship between knowledge workers, banking work environment and productivity of commercial banks in Kuching / Chong Fen Nee and Chong Vui Hok (Universiti Teknologi MARA, Sarawak, 2004)
This study seeks to understand the relationship between knowledge workers, the banking work environment and the impact of the work environment on the productivity of the commercial banks in Kuching. Information for the study was collected through two sets of questionnaires. Among the findings of the study were that bank employees generally fitted the definition of knowledge workers. However, their being non-avid readers of serious and intellectually stimulating reading materials threatens this status. The findings of the study also supported the long held belief that staff are an organisation's greatest assets. Further, it was found that there was room for improvement in terms of enhancing the conduciveness of the banking work environment, the management of knowledge workers and knowledge management for improved banking productivity and competitive edge.